ANALISIS HUKUM KEBIJAKAN KELEBIHAN DIMENSI DAN KELEBIHAN MUATAN TERHADAP DEMONSTRAN GERAKAN SOPIR JAWA TIMUR - Irvan Abu Arifaini; Hari Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study aims to provide an overview of the implementation of controlling excess freight, namely the Zero ODOL policy and its impact on business actors and changes in prices for basic necessities and essential goods. connecting cities with one another, so that it can also lead to an increase in the flow of vehicular traffic as a means of distribution and mobility of both people and goods. In order to avoid the occurrence of overloading of goods transport, every freight car carrying cargo is required to weigh its cargo at the weighbridge. This research uses normative research methods, namely research that examines the study of documents and archives, using secondary data such as legal theory, statutory provisions, and opinions from previous graduates. This research was conducted by analyzing the principles, theories and legal concepts as well as statutory provisions related to the online licensing system in terms of trading of unlabeled snacks through online shopping platforms. The problem that occurs in this study is that there are still many distributions of unlabeled snacks that have the potential to harm consumers. Researchers formulate a new concept that has been analyzed in various ways to find legal certainty regarding the management of the licensing system for trade in unlabeled snacks, where in this case the rights of consumers are still not properly fulfilled and the obligations of business actors are not carried out properly. and right. In order to maintain road infrastructure, reduce the number of traffic accidents and reduce victims of traffic accidents due to vehicles with overloads and/or oversize violations, on October 11, 2019 the Minister of Transportation issued Circular Letter Number: SE 21 of 2019 concerning Supervision of High-Quality Cars. Overloading Infringement and/or Over Dimension Violation. The implementation of policy supervision without ODOL (Zero ODOL) is carried out based on a mutual agreement between ministries, namely the Ministry of Transportation, the Ministry of PUPR, the Ministry of Industry, the Ministry of SOEs, the Indonesian National Police, and the Industrial Association.